2018
DOI: 10.7752/jpes.2018.s2148
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study aimed to investigate Physical Education (PE) students' belief systems toward the four important curricula outcomes goals (physical activity and fitness, self-actualization, motor skill development and social development) and to compare these beliefs according to gender and undergraduate Faculty program attended. Method: 690 Students from the three major PE Faculties in Greece were enrolled (465 males, 225 females). They completed a previously validated four-factor belief systems instrument. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…To provide more focus on content related to physical activity, as opposed to movement competency, Kulinna and Silverman [18,19] developed a valid and reliable instrument, underpinned by educational and psychological theories (e.g., social cognitive theory, self-efficacy) that was capable of assessing a teacher's attitude towards physical activity and fitness. Subsequent instrument validation work on the curricular outcome goals for physical education has been conducted by Adamakis and colleagues [20][21][22][23], and Guan, McBride, and Xiang [24]. These studies confirmed the presence of a four factor model (physical activity and fitness, self-actualisation, motor skill development, and social development) through internal consistency and confirmatory factor analysis.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…To provide more focus on content related to physical activity, as opposed to movement competency, Kulinna and Silverman [18,19] developed a valid and reliable instrument, underpinned by educational and psychological theories (e.g., social cognitive theory, self-efficacy) that was capable of assessing a teacher's attitude towards physical activity and fitness. Subsequent instrument validation work on the curricular outcome goals for physical education has been conducted by Adamakis and colleagues [20][21][22][23], and Guan, McBride, and Xiang [24]. These studies confirmed the presence of a four factor model (physical activity and fitness, self-actualisation, motor skill development, and social development) through internal consistency and confirmatory factor analysis.…”
Section: Introductionmentioning
confidence: 87%
“…This is due to the attention and focus by governments and researchers on the importance and promotion of physical activity behaviours amongst children and adolescents for both educative and health outcomes [10,31]. To date, there are only a few studies available in the literature examining these constructs [18][19][20]23]. Studying these is an important research area given the importance of the physical activity engagement of students during school health and physical education as well as the nature of teachers' pedagogical practices in affording or constraining such engagement.…”
Section: Introductionmentioning
confidence: 99%
“…The intentional choice of participants was privileged for a deeper understanding of the analyzed cases and considering the research questions . For this reason, preservice teachers were selected for convenience and criteria from previous research on epistemic beliefs, such as gender (Adamakis, 2018;Kulinna et al, 2010) and sports experience (Yildizer, 2020).…”
Section: Participantsmentioning
confidence: 99%
“…Muchas de las creencias que tienen las y los estudiantes universitarios/as de magisterio sobre la enseñanza de la Educación Física provienen de sus experiencias como alumnos/as (Adamakis, 2018). Como señala Zoglowek (2021) los propios docentes de Educación Física ven su campo de actividad como un trabajo divertido, sin exigencias ni cargas especiales, que permite convertir una afición en una profesión o un trabajo con alto riesgo de burnout.…”
Section: Introductionunclassified